Correlation between EFL Students Academic Achievement and Epistemic Beliefs in Relation to Educational Psychology Course - Kurniati, Elyisa; Emaliana, Ive (Journal of Languages and Language Teaching, 2025)
Educational psychology course and the epistemic beliefs of prospective teachers play a role in forming a competent teacher. While there is substantial literature exploring teachers’ epistemic belief, its interplay with course studies by prospective English teacher remains unclear. This research provides a novel understanding on the interplay of epistemic beliefs with educational psychology course, and achievement of prospective English teacher by integrating an explanatory sequential mixed methods design. Using quantitative survey to collect GPA (Grade Average Points), epistemic beliefs and perception of educational psychology, this study involve 102 EFL students at Brawijaya University through convenience sampling. Descriptive statistical and correlation analysis conducted in the first stage reveal their epistemic was moderate and their perception was high, and only between their epistemic beliefs and perception was found a strong correlation. Through confirming or disconfirming sampling, representative from the first stage participated in qualitative phase for semi-structured interview, resulting in justification of their positive perception and confirmation of the interconnection with epistemic beliefs. Findings imply there is a need to comprise aspects of high epistemic beliefs to have a more positive educational psychology course, that encourage adequate developmental feedback, active learning environments, inclusive advocacy, and student self-efficacy.. The high interest in unlisted content in the current module implies the need for material relevance of the course. The implication is for EFL teacher education to reconsider the content in educational psychology with students’ epistemic beliefs in order to equip English education students to become effective teachers.